Chemical profile of Eugenia brasiliensis (Grumixama) pulp by PS/MS paper spray and SPME-GC / MS solid-phase microextraction (Research, Society and Development, 2020)
The Eugenia brasiliensis, known as grumixama, is a fruit native to the Brazilian biodiversity and has characteristic flavor and aroma, bioactive compounds with antioxidant properties and benefical health characteristic. Since the consumer market is focused on the demand for products with natural and functional appeal, this study aimed to characterize the grumixama pulp, evaluate the antioxidant potential and trace chemical and volatile organic compounds of this fruit profile. For this purpose, analyzes of titratable acidity, pH, moisture, proteins, ash, fibers, total sugars, and lipids were performed. The determination of total phenolic compounds used the Folin-Ciocalteu method, and the antioxidant activity used the radical ABTS test. The characterization of the chemical profile consisted of obtaining fingerprints using Paper spray PS/MS and the extraction of volatile organic compounds employing solid-phase microextraction (SPME) using PDMS/DVB fiber and subsequent separation and identification by CG-MS. The grumixama pulp stood out for its acidity and high fiber content (20.34g/100g of pulp), in addition to presenting average levels of total phenolic compounds (173.85 ± 3.21 mg 100 g of pulp) and antioxidant activity (844.86 ± 2.03 mM/100g of pulp). Regarding the chemical profile of the pulp, 45 compounds were listed by PS/MS, with emphasis on flavonoids, phenolic compounds, carotenoids, sugars, catechins and quercetin derivatives. Nineteen volatile organic compounds can be identified, all of them belonging to the terpene class, 94.7% sesquiterpenes, and 5.3% monoterpenes, compounds that are responsible for several sensory characteristics of the fruits. The results showed that the association between the antioxidant activity promoted by the bioactive and the VOCs of the grumixama pulp make this fruit promising for acceptance in the market and can be added to various product elaborations, increasing its nutritional and functional value.